2019
DOI: 10.1177/0164027519860270
|View full text |Cite
|
Sign up to set email alerts
|

Religious Attendance, Religious Importance, and the Pathways to Depressive Symptoms in Men and Women Aged 50 and Over Living in Ireland

Abstract: Objectives: We aimed to explore the relationship between religiosity and depressive symptoms longitudinally. Method: We used four waves (2009–2016) of the Irish Longitudinal Study on Ageing (TILDA) to create growth curve models (GCM) of depressive symptoms and religious attendance/importance in a sample aged 50+ in Ireland and structural models to assess the longitudinal associations between religious attendance/importance and depressive symptoms. We tested whether this relationship was mediated by social conn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 38 publications
3
21
1
Order By: Relevance
“…Our study shows that applying religion to cope with stress has a protective dimension in a group of men with depression disorders. These results stay in contradiction to the findings of Orr et al ( 76 )—they found that higher initial religious engagement is associated with higher initial depressive symptoms, especially among men. A systematic review that examined the correlation of religion and suicide conducted by Koenig et al ( 77 ) found that most of the studies (84%) indicated fewer suicides or more negative attitudes toward suicide among the more religious people.…”
Section: Discussioncontrasting
confidence: 99%
“…Our study shows that applying religion to cope with stress has a protective dimension in a group of men with depression disorders. These results stay in contradiction to the findings of Orr et al ( 76 )—they found that higher initial religious engagement is associated with higher initial depressive symptoms, especially among men. A systematic review that examined the correlation of religion and suicide conducted by Koenig et al ( 77 ) found that most of the studies (84%) indicated fewer suicides or more negative attitudes toward suicide among the more religious people.…”
Section: Discussioncontrasting
confidence: 99%
“…Given that perceived distributive unfairness connects with the idea of inequality, evaluating the gender-contingent buffering effects of religion vis-a `-vis perceived distributive unfairness may shed light on the gendered aspects of the social inequality-religion dynamics. Third, previous literature documents that the mental health consequences of religion are gendered (Bierman, Lee, and Schieman 2018;Lee and Ang 2019;Orr et al 2019). Generally, this body of work demonstrates that women enjoy greater psychological benefits from religious involvement than men.…”
mentioning
confidence: 94%
“…The positive relationship between personal religiosity and various health outcomes among older adults has been well-documented (Bradshaw & Kent, 2018; Idler & Kasl, 1997; Orr et al, 2019). Compared with the abundance of findings at the individual level, however, research on the contextual effect of religiosity has been relatively scarce.…”
Section: Theoretical and Empirical Backgroundmentioning
confidence: 99%
“…Empirically, assessing the religious dimension is germane for our empirical data consisting of older European adults, since age and religiosity are positively correlated globally while Europe ranks lowest on multiple measures of religious commitment/engagement vis-à-vis other continents (Pew Research Center, 2018). Since religion offers substantial health benefits for older individuals (Bradshaw & Kent, 2018; Orr et al, 2019) who tend to be more religious (Krause, 2008; Norris & Inglehart, 2011), it is noteworthy to examine how the national religious context serves as a buffer against the harmful effects of ageism in some of the world’s least religious countries.…”
Section: Introductionmentioning
confidence: 99%